Privileged scaffolds in drug discovery - Fu, Caiyun; Li, Ning; Yu, Bin (Academic Press, 2023)
"Privileged Scaffolds in Drug Discovery is the most complete and up-to-date work in the area. Covering a wide range of privileged structures, it is a perfect reference for scientists involved in targeted drug development. The editors recruited experts from several prestigious Chinese institutions to cover the areas of antiviral drugs, chalcone, pyrimidine, (benz)imidazoles, natural product-derived privileged scaffolds, N-Sulfonyl carboxamides, kinase inhibitors, antitumor molecules, antineurodegenerative drugs, triazoles, oxazolidinone, indole and indoline scaffolds, tigliane diterpenoids, peptide and peptide-based drugs, quassinoids, and others including pseudonatural products, macrocycles, stable peptides and peptidomimetics. The book also explores scaffolds in drug molecules approved in recent years. Privileged Scaffolds in Drug Discovery is a complete reference for researchers in drug discovery and organic synthesis, in academic and corporate settings, who are investigating privileged structures upon which to base new drugs. Researchers in medicinal chemistry and chemical biology will also find the contents of this book valuable."